Evaluation for Fatsia japonica leaves extract (FJLE) as green corrosion inhibitor for carbon steel in simulated concrete pore solutions. (1st January 2023) - Wang, Qihui; Wu, Xiaodi; Zheng, Huahao; Liu, Li; Zhang, Qi; Zhang, Aomei; Yan, Zhitao; Sun, Yi; Li, Zuojin; Li, Xueming
Abstract: In this work, the corrosion inhibition properties of FJLE in chlorine–containing simulated concrete pore solution (SCPS) were investigated by aqueous extraction of FJLE leaves. Fourier Transform Infrared Spectrometer (FTIR) and High–Performance Liquid Chromatography (HPLC) were used to determine the main components of FJLE. The corrosion inhibition properties were tested by Electrochemical Impedance Spectroscopy (EIS) and Potentiodynamic Polarization Curves (Tafel). The experimental results suggested that the corrosion inhibition rate of FJLE reached 89.6% at 1000 mg/L, and the inhibition efficiency finally stabilized at 91.2% with increasing immersion time. Molecular Dynamics Simulations (MDS) demonstrated that FJLE could effectively adsorb on the carbon steel substrate and prevent chloride ions from erosion. Finally, the corrosion inhibition mechanism was clarified. In addition, Fatsia japonica are widely distributed and have the combined properties of eco–friendly and long–term efficient corrosion resistance suitable for the building and construction field. Graphical abstract: Image 1 Highlights: FJLE as eco-friendly corrosion inhibitor for carbon steel in simulated concrete pore solutions was studied. FJLE exhibited high inhibition efficiency in simulated concrete pore solutions. MDS methods were used to simulate the adsorption processes of inhibition molecules. Mechanism of corrosion inhibition of FJLE was studied on carbon steel samples.